The Effectiveness of Food Insecurity Screening in Pediatric Primary Care - Lane, Wendy Gwirtzman; Dubowitz, Howard; Feigelman, Susan; Poole, Gina (International Journal of Child Health and Nutrition, 2014)
Background: Food insecure children are at increased risk for medical and developmental problems. Effective screening and intervention are needed. Methods: Our purpose was to (1) evaluate the validity and stability of a single item food insecurity (FI) screen. (2) Assess whether use may lead to decreased FI. Part of a larger cluster randomized controlled trial, pediatric residents were assigned to SEEK or control groups. A single FI question (part of a larger questionnaire) was used on SEEK days. SEEK residents learned to screen, assess, and address FI. A subset of SEEK and control clinic parents was recruited for the evaluation. Parents completed the USDA Food Security Scale (“gold standard”), upon recruitment and 6-months later. Validity, positive and negative predictive values (PPV, NPV) was calculated. The proportion of screened families with initial and subsequent FI was measured. Screening effectiveness was evaluated by comparing SEEK and control screening rates and receipt of Supplemental Nutrition Assistance Program (SNAP) benefits between initial and 6-month assessments. Results: FI screen stability indicated substantial agreement (Cohen’s kappa =0.69). Sensitivity and specificity was 59% and 87%, respectively. The PPV was 70%; NPV was 81%. SEEK families had a larger increase in screening rates than control families (24% vs. 4.1%, p<0.01). SEEK families were more likely to maintain SNAP enrollment (97% vs. 81%, p=0.05). FI rates remained stable at approximately 30% for both groups. Conclusions: A single question screen can identify many families with FI, and may help maintain food program enrollment. Screening may not be adequate to alleviate FI.